Activation of the phenylpropanoid pathway in Citrus sinensis collapsed vesicles during segment drying revealed by physicochemical and targeted metabolomics analysis. (30th May 2023) - Wang, Jiajie; Hou, Jiao; Huang, Chunlian; Wang, Wei; Liu, Yaci; Zhang, Haoyue; Yan, Dandan; Zeng, Kaifang; Yao, Shixiang
Highlights: Lignin content increased by 135% while flavonoids content decreased by 27.5% upon vesicle collapse. Lignin synthesis was activated at transcription and enzyme activity levels upon collapse. Flavonoids synthesis was inhibited at transcription and enzyme activity levels upon collapse. Targeted metabolomics showed an over-accumulation of eight lignin precursors upon collapse. Metabolic flux was shuttled to the synthesis of lignin instead of flavonoids upon collapse. Abstract: Segment drying is a common internal physiological disorder in citrus fruit, and vesicles get granulated or collapsed. This study aimed to probe whether and how the phenylpropanoid metabolism changes in vesicles during collapse of blood orange ( Citrus sinensis cv. Tarocco). Vesicle collapse led to a decrease in the content of nutrients and flavonoids, while an increase in lignin content. This disorder was further associated with the increasing enzyme activities and gene expression levels of both the general phenylpropanoid pathway and branch pathway of lignin synthesis, while decreasing enzyme activities and gene expression levels of branch pathway of flavonoids synthesis. Targeted metabolomics analysis of 14 metabolites of the lignin pathway revealed that lignin precursors were accumulated in collapsed vesicles. We provide solid evidence that phenylpropanoid metabolism could be activated, and, intriguingly, metabolic flux may be shuttled to lignin precursors synthesis rather than flavonoids synthesis in vesicles during collapse of blood orange.